(untitled) (Revista de História da UEG (REVHIST), 2023)
We propose a new historical narrative about the construction of the chapel of Senhor Bom Jesus do Matozinhos in Vila do Príncipe (current city of Serro/MG). We analyzed two aspects: the documents of the Senate of the Chamber and records about the Brotherhood of Bom Jesus do Matozinhos, maintainer of the primitive temple; and the reconstruction of this temple by the new Brotherhood of Mercês and São Benedito, with problems for the approval of its commitment, revealing the daily life of the new brotherhood. It proposes a general and unifying concept of the new chapel, objectively linked to mechanical crafts, stigmatized as exercised by those of “infected blood”, influenced by the Casa dos Vinte e Quatro, of Lisboa. We use bibliographic research documents from archives in Brazil and Portugal. The result is the proof of a temple to honor the mechanical crafts and all those connected directly to them as slaves, freedmen and manual workers. Keywords: Colony Brazil. Mechanical crafts. Lay brotherhoods. Serro do Frio County. Vila do Príncipe.